Studi Kuantitatif Pada Tede Coffee Padang Tentang Pengaruh Inovasi Produk Terhadap Repurchase Intention - Wingka Pramestia Hendri; Dwi Pratiwi Wulandari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is based on some problem associated with repurchase intention at Tede Coffee. So, the purpose of this study is to investigate the Influence of Product Innovation on Repurchase Intention at Tede Coffee Padang. This research is a quantitative descriptive study with population 987 person, and the sample on this reseach is 91 respondents. And then get form purposive sampling technique the sample is consumen of Tede Coffee. The data collection method in this research uses a questionnaire with a Likert scale which has been tested for validity and reliability. The collected data was then analyzed using simple linear regression analysis with the help of SPSS (Statistical Product and Service Solution) software version 25.00. From the analysis results, it can be concluded that based on the t-test results, for innovation variables with a significant level of 0.000 < 0.05, it means that there is significant influence of product innovation on repurchase intention. According to the F-test with a significance level of 0.000 < 0.05, it means that product innovation simultaneously has a significant effect on repurchase intention. The product innovation variable influences the repurchase intention variable by 55.2%, while the remaining 44.8% is influenced by other variables.